Early Cretaceous volcanic rocks and Early Cenozoic extrusions of Cape Mary, Schmidt Peninsula, North Sakhalin: Geochemical study. - Simanenko, V P; Rasskazov, S V; Yasnygina, T A; Malinovsky, A I; Chashchin, A A (PANGAEA, 2007)
Early Cretaceous volcanic rocks of the Mariisky sequence and Early Cenozoic extrusive-vent rocks of the Mary Cape are exposed at the most northwest of the Schmidt Peninsula, North Sakhalin. In chemical composition, all the rocks are subdivided into four groups. Three groups include volcanic rocks of the Mariisky sequence, which consists, from bottom to top, of calc-alkaline rocks, transitional calc-alkaline-tholeiite rocks, and incompatible element-depleted tholeiites. These rocks show subduction geochemical signatures and are considered as a fragment of the Moneron-Samarga island arc system. Trace-element modeling indicates their derivation through successive melting of a garnet-bearing mantle and garnet-free shallower mantle sources containing amphibole; pyroxene; and, possibly, spinel. The mixed subduction and intra-plate characteristics of the extrusive vent rocks of the Mary Cape attest to their formation in a transform continental margin setting.
(Table 1) Chemical composition of volcanic rocks from the Mariisky sequence and extrusive vent rocks of the Mary Cape, Schmidt Peninsula (North Sakhalin)
Keywords: Aluminium oxide; Archive of Ocean Data; ARCOD; Barium; Caesium; Calcium oxide; Cerium; Chromium; Cobalt; Dysprosium; Erbium; Europium; Gadolinium; Hafnium; Holmium; ICP-MS, Inductively coupled plasma - mass spectrometry; Iron oxide, Fe2O3; Iron oxide, FeO; Lanthanum; Lead; Lutetium; Magnesium oxide; Manganese oxide; Neodymium; Nickel; Niobium; Phosphorus oxide; Potassium oxide; Praseodymium; Rock type; Rubidium; Sakhalin Island; Samarium; Sample position; Scandium; Shm-03/16; Shm-03/17; Shm-03/18; Shm-03/19; Shm-03/20; Shm-03/21; Shm-03/22; Shm-03/23; Shm-03/25; Shm-03/26; Shm-03/27; Shm-03/28; Shm-03/31; Shm-03/34; Shm-03/36; Shm-03/37; Shm-03/38; Silicon dioxide; Snm-03/24; Sodium oxide; Strontium; Sum; Tantalum; Terbium; Thorium; Thulium; Titanium dioxide; Uranium; Vanadium; Water in rock; Wet chemistry; Ytterbium; Yttrium; Zirconium